Template ecological analsyis of the narratives of partner's and family member's of women who consumed alcohol in pregnancy - Tsetse, Agrinette Nontozamo (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
Although there is increasing research on alcohol in South Africa, most of this work has an epidemiological focus. Very little research has explored alcohol use during pregnancy specifically from the perspective of the woman's partner or family member or focused on contextual risk factors beyond the pregnant woman. This information is important to ensure that interventions are formulated based on the social contexts within which drinking in pregnancy takes place and in guiding interventions that aim to prevent prenatal alcohol use, thereby preventing the occurrence of FASDs. This study was guided by Bronfenbrenner's Ecological Systems Theory to understand partners' and family members' perspectives of prenatal exposure within the actual environments in which alcohol use takes place. According to this theory, an individual exists within layers of social relationships: the family, intimate partners, friendships, and healthcare workers (microsystems), interactions among these microsystems, for example, interaction between healthcare workers and intimate partner and family and social workers (mesosystem), accessibility of alcohol in the neighbourhoods (exosystems), religion, culture and society (macro-systems) and changes of the individual and socio-historical context (chronosystem). The data were collected using a biographic narrative interpretive method of interviewing. Thirteen narratives interviews were conducted with partners and family members in a disadvantaged community in Buffalo City, Eastern Cape Province. The interviews were analysed using Template Analysis within the Ecological Systems Theory to interrogate the stories of partners and family members. According to participants, some of the reasons women consumed alcohol in pregnancy are: drinking habits before pregnancy that were difficult to break in pregnancy; women drank during the first trimester of their pregnancy because of unplanned pregnancy; women continued drinking throughout their pregnancies to cope with the emotional upset caused by the trauma of rape and losing loved ones, stress, receiving HIV-diagnosis in pregnancy, intimate partner violence, infidelity, rejection and denial of pregnancy from partners. After birth, some women continued drinking. Consequently, their children were taken away from them by social workers and family members because the parents were unable to care for the child due to alcohol use. There was lack of compliance of shebeens with liquor regulations, heavy drinking, high rates of alcohol use in pregnancy, and easy accessibility of alcohol within this study community. Pregnant women used religious coping beliefs to cope with their circumstances such as changes in their health, relationships and finances. Drinking during pregnancy is a complex problem that stems from multiple social and structural issues and interventions should therefore not only focus on the individual, but also on social networks and communities.
Keywords: Pregnant women -- Alcohol use -- Social aspects; Substance abuse in pregnancy; Fetus -- Effect of drugs on; Pregnancy -- Psychological aspects; Pregnant women -- Substance use; Substance abuse -- Social aspects; Ecological Systems Theory